DESAIN LEMBAR KERJA SISWA PADA PEMBELAJARAN STEM UNTUK SISWA SEKOLAH DASAR - Ghullam Hamdu; Nur Itsna Rostiana (Universitas Muria Kudus, 2020)
This study aims to find the right design that can be used by students in achieving 4C abilities (communication, collaboration, critical thinking, and creativity).This research is a Research and Development research with this research stage starting from needs analysis, drafting design, validation, testing and final revision. This research was conducted at two different elementary schools in the City of Tasikmalaya. The LKS test was conducted by describing the changes in the results of the LKS entries by grade 5 students in groups at two different elementary schools in the city of Tasikmalaya, West Java. The resulting design is a LKS that is based on the STEM learning stages and the revision LKS is based on the results of student entries in the LKS. The results of this LKS become an indication of how students can complete assignments by understanding the various commands or activities contained in the LKS in writing.